Online English Club for High School Students: Going Globa - Adaninggar Septi Subekti; Andreas Winardi; Arida Susyetina; Fransisca Endang Lestariningsih (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
The community service programme was conducted in the form of an English Club intended for high school students. The high school partner was SMA Immanuel Kalasan, Sleman, Yogyakarta Special Regency. A total of 13 students participated in this extracurricular activity. There were six online, synchronous meetings conducted once a week. Themed "Going Global", the programme aimed to not only facilitate the student participants to improve their English language but also to facilitate them to possess intercultural competence. It was hoped that they would consider globalisation era an opportunity to understand one another and to collaborate to achieve goals together. In practice, each meeting used the combination of a 60-90 minute synchronous Zoom session and asynchronous activities through tasks that should be completed and submitted before the next synchronous meeting. Seen from the indicators of attendance and submission of tasks, it could be stated that several participants were not very motivated to actively participate in the programme. However, seen from the qualitative testimonies of several participants, the programme was engaging and could provide them with meaningful learning. Based on the evaluation of the degree of success of the programme, several conclusions were suggested along with suggestions for future programmes’ improvements.